NEUTRONICS AND THERMAL HYDRAULICS ANALYSIS FOR FULL CORE CONVERSION OF THE DALAT NUCLEAR RESEARCH REACTOR - LUONG, BA VIEN; LE, VINH VINH; HUYNH, TON NGHIEM; NGUYEN , KIEN CUONG (Nuclear Science and Technology, 2011)
The paper presents all calculated results of neutronics and steady state thermal hydraulics for full core conversion from High Enriched Uranium (HEU) to Low Enriched Uranium (LEU) of the Dalat Nuclear Research Reactor (DNRR). The parameters of neutronics characteristics of two proposed working cores were investigated by using MCNP5, REBUS and VARI3D computer codes and for steady state thermal hydraulics PLTEMP3.8 was used to estimate cladding temperature, coolant temperature and ONB margin. Critical configuration cores were also established for DNRR with LEU fuels and minimum critical configuration core is loaded 66 fuel assemblies. Two proposed working cores with 92 LEU fuel assemblies and 12 Beryllium rods were considered more detailed on the neutronics, thermal hydraulics and utilization point of views. The analysis results affirmed that the DNRR loaded with LEU fuel has all safety features as HEU and mixed HEU-LEU fuel cores.